Integrated Reporting : Lessons from the South African Experience - Hanks, Jonathon; Gardiner, Louise (World Bank, Washington, DC, 2012)
One of the more significant recent governance trends is the global shift to integrated reporting. This article offers historical background and practical guidance for company directors and executives as they approach this relatively new way of communicating with stakeholders. The authors draw on insights and experience gained in advising some of South Africa's top companies on integrated reporting as these companies respond to the King Code of Governance Principles for South Africa 2009 (King III) and the listing requirement of the Johannesburg stock exchange (that all companies issue an 'integrated report' for financial years starting on or after March 1, 2010 or explain why they are not doing so).